Delineation of Pseudomonas savastanoi pv. savastanoi strains isolated in Tunisia by random-amplified polymorphic DNA analysis - Krid, S.; Rhouma, A.; Quesada, Jose M.; Penyalver, Ramón; Gargouri, A. (2017)
To investigate the genetic diversity of Pseudomonas savastanoi pv. savastanoi strains and to look whether these strains were distributed to geographical location. Random amplification of polymorphic DNA (RAPD) was used to discriminate between 58 Tunisian strains and 21 strains from various other countries of P. savastanoi pv. savastanoi, the causal agent of olive knot disease. Isolates were separated into three groups by cluster analysis and principal coordinate analysis of RAPD fingerprint data obtained with three primers (OPR-12, OPX-7 and OPX-14). Group 1 contained isolates from the southeast of Tunisia and European strains. Group 2 comprised strains isolated from the north of Tunisia exclusively while group 3 encompassed the majority of isolates obtained from five orchards located in the centre of Tunisia. The results indicated that isolates of P. savastanoi pv. savastanoi were genetically distinct according to geographic regions. RAPD grouped isolates derived from the same orchard as identical. This is the first application of RAPD in the delineation of P. savastanoi pv. savastanoi strains.